Japan Society of Hepatology guidelines for sarcopenia in liver disease (1st edition): Recommendation from the working group for creation of sarcopenia assessment criteria. Issue 10 (September 2016) - Nishikawa, Hiroki; Shiraki, Makoto; Hiramatsu, Akira; Moriya, Kyoji; Hino, Keisuke; Nishiguchi, Shuhei
Abstract : Sarcopenia is defined by muscle loss and muscle dysfunction. Sarcopenia is classified into primary and secondary types, based on the cause. Primary sarcopenia is mainly aging‐related sarcopenia, whereas secondary sarcopenia is the reduced muscle mass and strength that accompanies an underlying disease. Given the essential role of the liver in metabolism, secondary sarcopenia due to nutritional disorders or other factors can frequently occur in liver disease. In 2015, the Japan Society of Hepatology (JSH) decided to establish its own assessment criteria for sarcopenia in liver disease because the number of liver disease patients with sarcopenia is expected to increase and there is cumulative evidence to indicate sarcopenic patients have poor clinical outcomes. A working group to create assessment criteria for sarcopenia has thus been established by the JSH. In this article, we summarize the current knowledge with regard to sarcopenia and present the assessment criteria for sarcopenia in liver disease proposed by the JSH (1st edition). To the best of our knowledge, this is globally the first proposed assessment criteria for sarcopenia specializing in liver disease.